2002
DOI: 10.1017/s0714980800000611
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Family Caregivers: Implications for Professional Practice

Abstract: The formal sector's increasing recourse to families poses questions concerning the type and degree of participation that is expected of family caregivers and the conceptions that exist regarding them. This article examines different conceptions and their implications for practice, based on reflexions emanating from the authors' 15 years of empirical research on caregiving. A typology of practice approaches based on the various conceptions is presented including: the dependent adult approach, the caregiver as j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 19 publications
(30 reference statements)
0
31
0
4
Order By: Relevance
“…How professionals perceive families with respect to their responsibilities and obligations towards the elderly people for whom they care has an important bearing on their experience of formal support services. For example, they may be perceived as co‐clients, co‐workers and partners, or more often, as background and taken‐for‐granted resources (Twigg & Atkin 1994, Guberman & Maheu 2002). The political context in which formal support is provided in Ontario means that families are perceived, and indeed, written into legislature as background resources.…”
Section: Discussionmentioning
confidence: 99%
“…How professionals perceive families with respect to their responsibilities and obligations towards the elderly people for whom they care has an important bearing on their experience of formal support services. For example, they may be perceived as co‐clients, co‐workers and partners, or more often, as background and taken‐for‐granted resources (Twigg & Atkin 1994, Guberman & Maheu 2002). The political context in which formal support is provided in Ontario means that families are perceived, and indeed, written into legislature as background resources.…”
Section: Discussionmentioning
confidence: 99%
“…When support is needed however, most (75 to 90 percent) is provided by family members (Guberman and Maheu 2002). Spouses are the most important source of informal support, followed by adult children (typically daughters, but also sons) (Campbell and Martin-Matthews 2000).…”
Section: Informal Caregivingmentioning
confidence: 99%
“…A new UK study has indicated that, while women continue to provide the bulk of care in the home and community, an increasing number of men are now heavily involved in caregiving, particularly within their own household (Hirst 2001). However, the transfer of responsibility from institutions to home has not necessarily been accompanied by effective service allocation and support to family carers (Guberman & Maheu 2000, 2002, Lavoie et al . 1998), even where policy and legislative frameworks mandate this (Fruin 1998, Arksey et al .…”
Section: Introductionmentioning
confidence: 99%